Qualidade de uma vida de mulheres com câncer de mama em quimioterapia neoadjuvante - Vianna, Ana Márcia Sanches de Almeida (2015)
Breast cancer is the second most frequent type of cancer, only preceded by skin cancer. Although considered of good prognosis, it is still a stigmatizing condition. Objective: To characterize demographic aspects and quality of life (QoL) of women with breast cancer before and after treatment with neo-adjuvant chemotherapy at a teaching hospital in the state of São Paulo. Methodology: descriptive, cross-sectional study. Patients: participants were 60 adult women starting neo-adjuvant chemotherapy AC (Adriamycin + Cyclophosphamide). For data collection the following instruments were used: Identification Card, Interview Guide and Functional Assessment of Cancer Therapy (FACT-B). Data were qualitative and quantitatively analyzed with descriptive statistics. For comparative analysis between variables the Wilcoxon test was used with significance level of p<0.05. Results: Participants ages ranged from 27 to 83 years old (M = 52.42 years, SD = 12.66 years), married (61.7%), with children and attending primary school (75%). For the physical, and functional domain, TOI (Trial Outcome Index), FACT-G (Functional Assessment of Cancer Therapy – General) and FACT-B there was a significant difference in the assessment of QoL pre and post-QT. Feeling unattractive (58.3%), sexual dissatisfaction (56.6%), insomnia (53.3%), alopecia (52.3%), fatigue (43.3%), inability to experience pleasure in life (40%) and feelings of sadness (41.6%) and inability to work (35%) were the most frequent symptoms post-QT. Conclusion: QT has an important impact on physical and functional QoL, impairing several roles played by the patient and affecting sexual and affective relationships.